Factors associated with mortality among patients admitted to King Narai Hospital due to acute upper gastrointestinal bleeding - Sirisunhirun, Pavapol (Journal of Medicine and Health Sciences, 2024)
Acute upper gastrointestinal bleeding (UGIB) is a significant public health concern and a leading cause of death worldwide. Data from King Narai Hospital over the past 5 years reveals that the mortality rate ranged between 9-14%. This study aimed to investigate the factors associated with mortality among patients admitted to King Narai Hospital due to acute UGIB. The study group consisted of 204 individuals diagnosed with acute upper gastrointestinal bleeding between January 2023 and December 2023. The research tool used was a data recording form that included demographic and clinical data, laboratory parameters, endoscopic findings, and treatment outcomes. Data were analyzed using descriptive statistics and multiple logistic regression. The results revealed that there were 204 cases of patients with acute UGIB, with 122 patients (59.8%) being male. The median age was 61±15.06 years. A history of aspirin use was found in 30.4% of cases. Most patients presented with melena, accounting for 110 cases (53.9%), while hematemesis was found in a total of 94 cases (46.1%). Mortality occurred in 35 cases (17.15%). Of those who died, 51.4% had undergone esophagogastroduodenoscopy. Esophageal varices and peptic ulcers were found in 9 cases (50%) and 8 cases (44%), respectively. Significant factors associated with mortality in acute UGIB patients included a pulse rate higher than 100 beats per minute, a systolic blood pressure lower than 90 mmHg, a white blood cell count greater than 12.00x109 cells per liter, lack of access to endoscopy, and provision of more than 3 units of fresh-frozen plasma (FFP). In conclusion, esophageal varices and peptic ulcers were the main causes of death. Factors that increase the risk of mortality include a pulse rate of more than 100 beats per minute, a systolic blood pressure lower than 90 mmHg, a white blood cell count of more than 12.00x109 cells per liter, lack of access to endoscopy, and the delivery of more than 3 units of FFP.